2019
DOI: 10.1186/s40814-019-0496-4
|View full text |Cite
|
Sign up to set email alerts
|

Home management of lower limb lymphoedema with an intermittent pneumatic compression device: a feasibility study

Abstract: Background Lymphoedema is a chronic condition that causes swelling in the body tissues. Presently, there is no cure for lymphoedema; instead, current treatment is aimed at lifelong management to help control symptoms. Intermittent pneumatic compression (IPC) therapy can be considered as an adjunct to standard lymphoedema care; however, research regarding the efficacy of this treatment modality is limited. Methods Twenty participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…8 , 26 Two previous studies examined usability of PCD for lymphoedema: one included lower limb therapy and the other, treatment of the head and neck. 25 , 27 Both utilized a rating scale to determine device usability. This was also the approach taken in our study, which found that the use of the new PCD system was both comfortable and feasible for a single session.…”
Section: Discussionmentioning
confidence: 99%
“…8 , 26 Two previous studies examined usability of PCD for lymphoedema: one included lower limb therapy and the other, treatment of the head and neck. 25 , 27 Both utilized a rating scale to determine device usability. This was also the approach taken in our study, which found that the use of the new PCD system was both comfortable and feasible for a single session.…”
Section: Discussionmentioning
confidence: 99%
“…1 ), was designed to build on an earlier feasibility study, which utilized IPC delivered by the LymphAssist compared with a control group. 12 Ethical approval for this study was obtained from the appropriate local National Health Service Research Ethics Committee (LREC No. 18/WA/0114) and registered with ClinicalTrials.gov.…”
Section: Methodsmentioning
confidence: 99%
“…Participants ( n = 40) with primary ( n = 1) or secondary ( n = 39) lymphedema were recruited from two outpatient lymphedema clinics in the South East Wales area. 12 All participants had a confirmed diagnosis of stage II or III lower limb lymphedema as defined by the International Society of Lymphology; 33 participants had bilateral lower limb disease and 7 had unilateral. 13 All participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements were made utilizing a metric nonstretch tape measure (Medi Ltd, Germany). Leg circumference was measured at several points starting just above the malleolus and then at 4 cm intervals ascending the leg to the knee (the distal leg), and then from above the knee up to the upper thigh (the proximal leg) 5,6 . A portable hand‐held myotonometer (Myoton AS, Tallinn, Estonia) was used to quantitatively assess the skins mechanical and viscoelastic properties 9 .…”
Section: Methodsmentioning
confidence: 99%